Man dies, wife injured in first trip outside India - Alagesh, T.N. (The New Straits Times Press (M) Bhd, 2015)
It was the couple's first foreign visit. Their youngest son had invited them to witness him receiving his electrical and electronics engineering doctorate scroll at University Malaysia Pahang (UMP) here.